HER2 testing of gastro-oesophageal adenocarcinoma: a commentary and guidance document from the Association of Clinical Pathologists Molecular Pathology and Diagnostics Committee. Issue 5 (8th February 2018) - Wong, Newton A C S; Amary, Fernanda; Butler, Rachel; Byers, Richard; Gonzalez, David; Haynes, Harry R; Ilyas, Mohammad; Salto-Tellez, Manuel; Taniere, Philippe
Abstract : The use of biologics targeted to the human epidermal growth factor receptor 2 (HER2) protein is the latest addition to the armamentarium used to fight advanced gastric or gastro-oesophageal junction adenocarcinoma. The decision to treat with the biologic trastuzumab is completely dependent on HER2 testing of tumour tissue. In 2017, the College of American Pathologists, American Society for Clinical Pathology and the American Society of Clinical Oncology jointly published guidelines for HER2 testing and clinical decision making in gastro-oesophageal adenocarcinoma. The Association of Clinical Pathologists Molecular Pathology and Diagnostics Committee has issued the following document as a commentary of these guidelines and, in parallel, to provide guidance on HER2 testing in National Health Service pathology departments within the UK. This guidance covers issues related to case selection, preanalytical aspects, analysis and interpretation of such HER2 testing.